TRANSFORMASI DIGITALISASI PENDIDIKAN DAN KESEJAHTERAAN PADA ERA COVID-19 : KAJIAN SYSTEMATIC LITERATURE REVIEW - Dudi Duta Akbar (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
COVID-19 has caused many difficulties around the world, from productivity to educational problems. This research aims to disseminate research trends on digitalization of education and welfare in the context of the COVID-19 pandemic. Through a systematic review, all the most research works on this topic in English, context, which were published between 2020–2023 in international high-impact journals, were analysed. After analyzing 201 articles, the results show the most frequently used keywords arehuman covids digitalization education sustainability. Research that directly discusses the transformation of digitalization on welfare was not found. This is transmitted to the points above to achieve the impact of digitalization of education on welfare.